PENGARUH FAMILY EMPOWERMENT TERHADAP SELF CARE PASIEN STROKE - Husna, Elfira; Hidayati, Hidayati (LPPM Universitas Prima Nusantara Bukittinggi, 2022)
Background: Stroke or brain attack is the sudden death of several brain cells and disease with the second leading cause of death worldwide and the third disease that causes disability. The Greatest burden of Stroke Survivors is long-term sequelae or physical disabilities due to neurological disorders. Physical disability causes stroke patients to experience dependence on fulfilling self-care. In the end, this can cause disturbed family function.Aims: This study aims to determine the effect of family empowerment on self-care for stroke patients.Methods: The research design is Quasi-Experimental Pre and Post-test with two groups. the sample in this study is 26 people with stroke and their families as a caregiver, who received Therapy Empowerment for as many as 13 patients, and the control group was as many as 13 patients. The using Instrument is Self Care Indeks Barthel. The data collected is processed using the dependent T-test (paired sample T-test), that is, if the value of the degree of confidence is 95% or ? 0.05.Result: The results showed a significant increase in self-care stroke patients who received Empowerment Therapy compared with a group who did not get therapy (P-value ? 0.05).Conclusion: Empowerment Therapy is recommended to improve Self Care for patient's stroke